PENGARUH PENAMBAHAN SERBUK CANGKANG KEONG TERHADAP NILAI CBR TANAH LEMPUNG EKSPANSIF - Hastuti, Yulia; Muhtarom, Ahmad; Iryani, Sakura Yulia; Derisqi, Azmi; Dewi, Ratna (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
n this research, soil improvement is done by using waste of snail shells (LCK) in Desa Ulak Kembahang II, Kecamatan Lubuk Keliat, Kabupaten Ogan Ilir, Sumatera Selatan and soil from Tanjung Api-api Area, Gasing , Kabupaten Banyuasin, Sumatera Selatan . The soil used is a type of problematic soil that is expansive clay, which is known LL value (Liquid limit) more than 35%. The LCK used is then used as powder. Furthermore, there are 5 variations of percentage of addition of snail shell powder (SCK) with soil, and give the curing time is for 0, 1 and 7 days. Results from CBR Unsoaked (US) Testing resulted in the addition of SCK at a certain percentage and the curing time could increase the value of CBR expansive clay soil. The highest value of CBR Unsoaked on variation of percentage of SCK increase as much as 11% in the curing curing time for 7 days that is equal to 5.6% for the value of CBR US which in the original land has a CBR value of 3.5%. The result analysis of SEM-EDX test on soil mixture and SCK known SCK works as filler which fill the cavity found in soil grains and the main element of soil known as SiO2 and Al2O3 forming binder material with CaO.